Current Promising Biomarkers and Methods in the Diagnostics of Antiphospholipid Syndrome: A Review - Bradacova, Pavla; Slavik, Ludek; Ulehlova, Jana; Skoumalova, Adela; Ullrychova, Jana; Prochazkova, Jana; Hlusi, Antonin; Manukyan, Gayane; Kriegova, Eva (Biomedicines, 2021)
Antiphospholipid syndrome (APS) is a hypercoagulation condition associated with the incidence of heterogenic antiphospholipid antibodies (aPLs), which non-specifically affect hemostasis processes. APS is clinically manifested by recurrent arterial and venous thromboses and reproduction losses. The aPL antibodies, which may induce clinical manifestations of APS, include criteria antibodies anti-cardiolipin, anti-β2-glycoprotein-I, and lupus anticoagulant, but also non-criteria antibodies, for example anti-β2-glycoprotein-I domain I, anti-phosphatidylserine/prothrombin, anti-annexin V, and many others. APS occurs mostly in patients of younger and middle age, most frequently in females. Laboratory diagnostics of APS are quite difficult, as they include a wide spectrum of examining methods, which are based on various principles of detection and are performed using various laboratory techniques. The objective of the review is to describe the current state of potentially examined biomarkers and methods in APS diagnostics. The aforementioned biomarkers are lupus anticoagulant, anti-β2-glycoprotein-I, anti-cardiolipin, anti-β2-glycoprotein-I domain I, anti-phosphatidylserine/prothrombin, anti-β2-glycoprotein-I IgA, anti-cardiolipin IgA, anti-annexin V and II, anti-prothrombin, anti-cardiolipin/vimentin, anti-protein S/protein C, and antibodies against phospholipid antigens for whose diagnostics we may use some of the methods established for a long time and some of the modern methods-the coagulation method for the determination of lupus anticoagulant (LA), enzyme-linked imunosorbent assay (ELISA), chemiluminescence analysis (CLIA), multiplex fluorescence flow immunoassay (MFFIA), fluorescence enzyme immunoassay (EliA), line immunoassay (LIA), multiline dot assay (MLDA), and thin-layer chromatography (TLC). Conclusion: Antibodies against phosphatidylethanolamine, phosphatidic acid, phosphatidylserine, phosphatidylinositol, cardiolipin/vimentin complex, and annexin V are currently the most studied new markers. However, these assays have not been standardized until now, both from the laboratory and clinical point of view. In this review we summarize the evidence of the most studied aPL markers and their potential clinical significance in seronegative APS (SN-APS).